Pray the gay away: identity conflict between Christianity and sexuality in Hong Kong sexual minorities. Issue 12 (1st December 2016) - Ho, Petula Sik Ying; Hu, Yiqian
Abstract: Recognition and respect for sexual minorities in Hong Kong is still a contested area. Public sexual identity politics in Hong Kong has been framed by traditional Chinese gender ideology and imported Christian beliefs which are profoundly negative. Focusing on the interpersonal relationships in three spheres of life, the research adopted the sociological perspective of personal life and the feminist geographers' idea of spatialization of identity management to analyze how the sexual self of sexual minorities has been marginalized and excluded in intimate social spaces of family, church communities and schools in Hong Kong with specific spatial practices and different forms of power/knowledge. By examining overlooked intimate injustice in personal life, this study illustrates that identity conflicts between Christianity and non-heterosexuality in everyday life is constructed through misrepresentation, misrecognition, harassment and exclusion in intimate relationships. Different types of knowledge are being used to reiterate pre-existing norms and institutionalized patterns of cultural value that constitute the sexual minorities as comparatively unworthy of respect. These micro-political processes involve both conformity and resistance to gender and sexual stereotypes. Participants managed to develop spatial coping strategies such as concealment, compartmentalization, confrontation and alternative sources of support to manage their lives with dignity and self-esteem.